An empirical study of unethical earnings management behaviors in Gulf Cooperation Council (GCC) listed firms - Kazma, Badih; Valax, Marc (Management international / International Management / Gestiòn Internacional, 2024)
We present an empirical rationale and supporting study revealing how executives, especially in the Gulf Cooperation Council(GCC) listed companies, resort to unethical earnings management practices in times of financial loss and financial distress. Employing a quantitative approach, this study analyzes 120 listed companies using the Modified Jones (1995) Model to estimate earnings management as a dependent variable. Regression analysis is employed to explore the impact of independent variables. Our findings conclude that executives across six GCC countries engage in earnings management through both positive and negative discretionary accruals. Notably, the results reveal that factors such as consolidation, financial distress and performance significantly influence earnings management practices.